Peran Pelatihan Muhadhoroh Dalam Meningkatkan Kemampuan Komunikasi Santri di Arrisalah Islamic International College - Sugesti Riza Nor Aida Riza; Musthofa; Ahmad Arifi (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
Some students still lack confidence in speaking in public. With muhadhoroh activities, students are taught and trained to be brave enough to speak in public in order to improve communication. The purpose of this study was to determine the implementation of muhadhoroh, the role of muhadhoroh in improving students' communication and its supporting and inhibiting factors at Pondok Modern Arrisalah Islamic International College. This research method uses a qualitative approach with a descriptive type. The technique of collecting data in this research uses interview, observation and documentation techniques. While the data analysis technique uses data reduction, data presentation and drawing conclusions. The results of the discussion of this study explain that (1) muhadhoroh at Pondok Modern Arrisalah has three stages, namely the planning stage, the implementation stage and the evaluation stage. (2) the role of muhadhoroh in improving the communication of students at Pondok Modern Arrisalah is to grow the mentality of the students, improve communication using foreign languages, more active communication, creating da'wah innovations. The supporting factors for muhadhoroh in improving students' communication are the Speech Contest Week Program (PLP), appreciation and appreciation, guidance from supervisors, methods according to needs, facilities and infrastructure, non-verbal communication and the inhibiting factor is that at least students know the importance of the muhadhoroh program , students' different foreign language skills, lack of self-confidence, lack of discipline of students. The conclusion is that muhadhoroh training has an important role for the students of Pondok Modern Arrisalah, one of which is to improve communication.